2012
DOI: 10.1007/s10103-012-1061-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light emitting diode (LED) therapy at 940 nm on inflammatory root resorption in rats

Abstract: The effects of LED therapy at 940 nm on periodontal healing, inflammatory cell infiltration, and root resorption were analyzed in an experimental model of orthodontic tooth movement in rats. Twenty-five male Wistar rats were allocated into four experimental groups: Control animals (Co, n = 5), Controls + LED therapy (CoLED, n = 6), animals submitted to orthodontic force (RR, n = 7) and submitted to orthodontic force + LED therapy (RRLED, n = 7). All procedures were approved by the Committee for Ethics in Anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 42 publications
2
35
1
10
Order By: Relevance
“…The movement was achieved with a nickel titanium spring and 50 g of force on the upper first molars. 15 The results presented an increase of periodontal tissue repair, reduced inflammation and reduced root resorption by phototherapy, thus contradicting the results of the present study. Despite the fact that the methodology was distinct, the difference found between these two studies could be due to different doses and wavelengths employed.…”
Section: Low-level Laser On Orthodontically Induced Root Resorptioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The movement was achieved with a nickel titanium spring and 50 g of force on the upper first molars. 15 The results presented an increase of periodontal tissue repair, reduced inflammation and reduced root resorption by phototherapy, thus contradicting the results of the present study. Despite the fact that the methodology was distinct, the difference found between these two studies could be due to different doses and wavelengths employed.…”
Section: Low-level Laser On Orthodontically Induced Root Resorptioncontrasting
confidence: 99%
“…[18][19][20] This review found only one study that assessed the phototherapy on the inflammatory root resorption, but with LED. 15 Considering that LED and laser phototherapy exhibit similar effects 21 and the coherence of light generate a benefit particularly in the deeper tissue layers, 22 these studies were compared. Fonseca et al 15 investigated the effect of phototherapy on inflammatory root resorption, in Wistar rats.…”
Section: Low-level Laser On Orthodontically Induced Root Resorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,4,5,[7][8][9][10][11][12][14][15][16][17][18]20,[23][24][25][26] We describe four fundamental points for experimental models to ensure that the evaluation of the effects of medication and phototherapy on induced tooth movement and associated root resorption is free of external influence.…”
Section: Palavras-chavementioning
confidence: 99%
“…This process results in beneficial therapeutic outcomes including but not limited to the alleviation of pain or inflammation, immunomodulation, and promotion of wound healing and tissue regeneration.^ [1]. PBM therapy was found to have multiple clinical benefits, which includes reducing pain [2][3][4][5][6][7], improving wound healing [8][9][10][11], accelerating bone healing [12][13][14][15][16][17], promoting osteointegration [18], facilitating orthodontic tooth movement [19][20][21][22][23][24][25][26], stimulating bone formation [27][28][29][30][31], and improving periodontal tissue repair and decreasing inflammation and root resorption [23,26,32]. The light sources were laser or a light-emitting diode (LED).…”
Section: Introductionmentioning
confidence: 99%